STRATEGI PDI-PERJUANGAN DALAM PEMILU PRESIDEN DAN WAPRES TAHUN 2014 - Turtiantoro Turtiantoro (JURNAL ILMU SOSIAL, 2015)
Research entitle "PDI-Struggle Strategy in Central Java in General Election of President and Vice President in 2014" is a qualitative research that momentum Presidential Election 2014. This study begins from the observation of the PDI-P in Central Java province in Pilgub in 2013 who  take a decision to nominate candidates for the pair of internal party, namely Ganjar Pranowo and Heru Sudjatmoko. The success of the PDI-P in the year 2013 was also continued with victory in the legislative elections held in april 2014, PDI-P Central Java Province scooped 27 seats, up four seats compared to the 2009 election. Two such events have a strong attraction for study because in 2014 there was also a general election for president and vice president. On the one hand the PDI-Struggle Central Java two wins in the race for political office, on the other hand suffered two defeats in the presidential and vice presidential elections in 2004 and 2009. For this reason this study was conducted to determine the strategy chosen in the elections until the end proved to victory.